Genetic evidence implies that primary and relapsed tumors arise from common precursor cells in primary central nervous system lymphoma. Issue 1 (18th November 2018) - Hattori, Keiichiro; Sakata‐Yanagimoto, Mamiko; Kusakabe, Manabu; Nanmoku, Toru; Suehara, Yasuhito; Matsuoka, Ryota; Noguchi, Masayuki; Yokoyama, Yasuhisa; Kato, Takayasu; Kurita, Naoki; Nishikii, Hidekazu; Obara, Naoshi; et al.
Abstract : Primary central nervous system lymphoma (PCNSL) is a rare subtype of lymphoma that arises within the brain or the eyes. PCNSL recurs within the central nervous system (CNS) in most relapsed cases, whereas extra‐CNS relapse is experienced in rare cases. The present study aimed at identifying the presence of common precursor cells (CPC) for primary intra‐ and relapsed extra‐CNS tumors, and further assessing the initiating events in bone marrow (BM). Targeted deep sequencing was carried out for five paired primary intra‐ and relapsed extra‐CNS tumors of PCNSL. Two to five mutations were shared by each pair of intra‐ and extra‐CNS tumors. In particular, MYD88 mutations, L265P in three and P258L in one, were shared by four pairs. Unique somatic mutations were observed in all five intra‐CNS tumors and in four out of five extra‐CNS tumors. Remarkably, IgH clones in the intra‐ and the extra‐CNS tumors in two pairs were distinct from each other, whereas one pair of tumors shared identical monoclonal IgH rearrangement. In a cohort of 23 PCNSL patients, L265P MYD88 mutations were examined in tumor‐free BM mononuclear cells (MNC) in which the PCNSL tumors had L265P MYD88 mutations. L265P MYD88 mutations were detected by a droplet digital PCR method in nine out of 23 bone marrow mononuclear cells. These results suggest that intra‐ and extra‐tumors are derived from CPC with MYD88 mutations in most PCNSL, arising either before or after IgH rearrangement. The initiating MYD88 mutations may occur during B‐cell differentiation in BM. Abstract : It was suggested that primary intra‐central nervous system (CNS) tumors and relapsed extra‐CNS tumors are derived from common precursor cells with MYD88 mutations in most primary CNS lymphomas. The initiating MYD88 mutations may occur during B‐cell differentiation in BM.